In vivo confocal microscopy of the abnormal cornea: a clinical and clinico-pathological correlation - Alomar, Thaer Saad (2012)
In vivo confocal microscopy (IVCM) offers a unique real time non-invasive imaging method to explore live tissues at cellular and subcellular levels of histological detail with magnifications very much comparable to conventional ‘ex vivo’ light microscopy. Therefore it has been widely used over the past two decades to investigate the ocular surface and cornea in health, disease and following surgical procedures. One of the main challenges in understanding IVCM is to get a proper interpretation of the images that present various figures and patterns of tissue structures all in black and white with variable degree of reflectivity, being whiter (or brighter) when they are more (or hyper) reflective. The lack of good correlation between IVCM and corresponding light microscopy for the same tissue samples has lead to speculative interpretations of IVCM images in the literature.